Characterization of Distinct CyanoHABs-Related Modules in Microbial Recurrent Association Network - Chun, Seong-Jun; Cui, Yingshun; Lee, Chang Soo; Cho, A Ra; Baek, Kiwoon; Choi, Ahyoung; Ko, So-Ra; Lee, Hyung-Gwan; Hwang, Seungwoo; Oh, Hee-Mock; Ahn, Chi-Yong (Frontiers in Microbiology, 2019)
To elucidate the interspecies connectivity between cyanobacteria and other bacteria (non-cyanobacteria) during cyanobacterial harmful algal blooms (cyanoHABs), samples were collected from the Nakdong River, Korea, from June 2016 to August 2017, and microbial recurrent association network (MRAN) analysis was performed to overcome the limitations of conventional network analysis. Microcystis blooms were tightly linked with Pseudanabaena in summer and were accompanied by significant changes in the non-cyanobacterial community composition (nCCC). Riverine bacteria could be clearly separated into modules that were involved in the formation, maintenance, and decomposition of cyanoHABs. Approximately one-fourth of the bacteria that were directly linked with major cyanobacteria acted as connectors or module hubs in cyanoHABs-related modules. The functional profiles of the cyanoHABs-related modules included nitrate reduction, aerobic ammonia oxidation, fermentation, and hydrocarbon degradation during the Microcystis bloom periods. In conclusion, the ecological network in relation to cyanoHABs appears to be highly dynamic; additionally, specific bacterial groups, or modules, contribute to the development and collapse of cyanoHABs. Furthermore, cyanoHABs were directly linked with many ecologically important keystone bacterial species that regulate the overall microbial network. Therefore, to understand cyanoHABs, a modular microbial perspective may be more helpful than a single bacterial species perspective.